POLICY OF THE SOVIET GOVERNMENT ON THE ORGANIZATION OF THE JUDICIAL SYSTEM (ON THE EXAMPLE OF THE SOUTHERN REGIONS OF UZBEKISTAN) - Ikhtiyor Khudoikulov (Western European Studies, 2025)
The article analyzes the policy of the Soviet government in establishing a judicial system in the southern regions of Uzbekistan. The study covers legal changes in the interwar period, the organizational structures of the judicial system, and their impact on socio-political life. The article also discusses the role of Soviet courts in supporting and implementing changes in society, as well as how these processes were perceived by the population
Keywords: Soviet government; Uzbekistan; southern regions